(3HjGf YdGeGJ BNQ GdReGfs - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3gPg QSGdI efbhdI ef GdNGJe GdeLJgO Hf GdTjN Ydi CjgG GdfGS SjXgQ ai BNQ GdReGf hbGFY JTjH dgG GdTHGf s
(3BNQgG (B:s
(3abGd Ydjg GdSdGe gPg GdCjI Ef Gddg YfOg Yde GdSGYI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B347 - (3U(B347s
(3GfXQ GdeNWhW Qbe (B292s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds